TGFBR2 coordinates the endometrial response to estrogen, regulating endometrial hyperplasia and fertility - Sydney E. Parks; Suni Tang; Anna Catherine Unser; Ananya L. Bhonsley; Eunbi M. Chung; Peixin Jiang; Audrey Savolainen; Vanessa J. Joseph; Dominique I. Cope; Ramya P. Masand; Renata Prunskaite-Hyyryläinen; Diana Monsivais (Proceedings of the National Academy of Sciences, 2025)
Proper endometrial function is critical for establishing and maintaining healthy pregnancies, as well as preventing the pathogenesis of conditions such as endometrial hyperplasia and endometrial cancer. The TGFβ signaling pathway regulates key aspects of endometrial biology, although the direct effects of many individual receptors remain unstudied. In this study, we characterize the role of TGFβR2 within the endometrium using a progesterone receptor-cre conditional knock-out mouse model ( Tgfbr2 flox/flox ; Pg r cre/+ ; “ Tgfbr2 cKO”). We found that conditional deletion of TGFβR2 resulted in female infertility, endometrial hyperplasia, altered estrogen and progesterone response, and, only in bred females, reproductive tract tumors. Pregnancy abnormalities in these females began in the prereceptive and implantation stages and compounded throughout gestation, presenting errors in decidualization, immune cell invasion, and early spiral artery formation. Tgfbr2 cKO females had endometrial epithelial hyperplasia at 13 to 14 wk of age, with a significant and region-specific reduction in glandular FOXA2 expression. While this hyperplasia did not advance to malignancy in virgin females, Tgfbr2 cKO females continuously bred for 6 mo all presented with reproductive tract tumors at the time of collection. Mechanistically, we show signaling via TGFβR2 attenuates estrogen signaling while bolstering progesterone signaling in the endometrial epithelium. By integrating ER and SMAD4 genome-wide binding studies with transcriptomic datasets, we demonstrate that both ER and SMAD4 are required for Pgr transcription. In this study, we highlight the importance of TGFβR2 in endometrial function and female fertility and shed light on the potential involvement of TGFβ signaling in estrogen and progesterone response regulation during early pregnancy.